Analisis Pengaruh Nilai Tukar Rupiah, Jumlah Uang Beredar Dan Tingkat Inflasi Terhadap Pertumbuhan Ekonomi Di Indonesia - Mathias Efi; Maria Indriyani Hewe Tiwu; Novi Theresia Kiak (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to find out and explain the analytical influence of the influence of the rupiah exchange rate, the amount of money in circulation and the inflation rate on economic growth in Indonesia. The type of research used by the researcher is quantitative research using secondary data. The data analysis techniques used include, multiple linear regression analysis, classical assumption test and hypothesis test using Eviews analysis tools. The results of the T test show that the exchange rate variable has a significant positive impact on Indonesia's economic growth, the money supply variable has a very large positive impact on Indonesia's economic growth, and the Inflation variable has a significant negative impact on Indonesia's economic growth. The results of the F test show that the exchange rate variable, the money supply variable, and the Inflation variable simultaneously have a significant effect on Indonesia's economic growth.